Helium transmission rate as a rapid and reliable method for assessing the water vapour transmission rate of transparent PET‐SiOx barrier foils. Issue 8 (2nd May 2021) - Herbst, Florian; Großer, Stephan; With, Patrick C.; Prager, Lutz; Pander, Matthias
Abstract : The graphical abstract shows the self‐made measuring setup consisting of two gas flow rate sensors for nitrogen and helium, a stainless‐steel flow cell with EPDM fittings and a single quadrupole mass spectrometer for the measurement of the HeTR Abstract : A single quadrupole mass spectrometer coupled measuring setup was developed for the investigation of the helium transmission rate (HeTR) of SiO x ‐coated polyethylene terephthalate (PET) barrier films. The setup allows the pressure‐less and time‐resolved measurements of the helium permeation at transient and steady‐state conditions. Whereas standard water vapour transmission rate (WVTR) experiments took extended test times (in the range of several days), HeTR measurements were finished after 1 h. For the material system investigated here, an excellent linear correlation of WVTR and HeTR was proven over two orders of magnitude (regarding WVTR). Experiments with application of different strain loads on the coated films revealed a significant increase of both, HeTR and WVTR. Scanning electron microscope (SEM) measurements evidenced multiple ruptures of the SiO x coating depending on the applied strain and initial thickness of the SiO x layer. Considering virgin barrier films and strain‐ruptured barrier films, a good correlation of WVTR and HeTR was shown.